Long-term mortality among kidney transplant recipients with and without diabetes: a nationwide cohort study in the USA. Issue 1 (7th May 2021) - Harding, Jessica L; Pavkov, Meda; Wang, Zhensheng; Benoit, Stephen; Burrows, Nilka Ríos; Imperatore, Giuseppina; Albright, Ann L; Patzer, Rachel
Abstract : Introduction: Little is known about the role diabetes (type 1 (T1D) and type 2 (T2D)) plays in modifying prognosis among kidney transplant recipients. Here, we compare mortality among transplant recipients with T1D, T2D and non-diabetes-related end-stage kidney disease (ESKD). Research design and methods: We included 254 188 first-time single kidney transplant recipients aged ≥18 years from the US Renal Data System (2000–2018). Diabetes status, as primary cause of ESKD, was defined using International Classification of Disease 9th and 10th Clinical Modification codes. Multivariable-adjusted Cox regression models (right-censored) computed risk of death associated with T1D and T2D relative to non-diabetes. Trends in standardized mortality ratios (SMRs) (2000–2017), relative to the general US population, were assessed using Joinpoint regression. Results: A total of 72 175 (28.4%) deaths occurred over a median survival time of 14.6 years. 5-year survival probabilities were 88%, 85% and 77% for non-diabetes, T1D and T2D, respectively. In adjusted models, mortality was highest for T1D (HR=1.95, (95% CI: 1.88 to 2.03)) and then T2D (1.65 (1.62 to 1.69)), as compared with non-diabetes. SMRs declined for non-diabetes, T1D, and T2D. However, in 2017, SMRs were 2.38 (2.31 to 2.45), 6.55 (6.07 to 7.06), and 3.82 (3.68 to 3.98), for non-diabetes, T1D and T2D, respectively. Conclusions: In the USA, diabetes type is an important modifier in mortality risk among kidney transplant recipients with highest rates among people with T1D-related ESKD. Development of effective interventions that reduce excess mortality in transplant recipients with diabetes is needed, especially for T1D.